Bridging the gap of axonal regeneration in the central nervous system: A state of the art review on central axonal regeneration - Costa, Gonçalo; Ribeiro, Filipa F.; Sebastião, Ana M.; Muir, Elizabeth M.; Vaz, Sandra H. (Frontiers in Neuroscience, 2022)
Neuronal regeneration in the central nervous system (CNS) is an important field of research with relevance to all types of neuronal injuries, including neurodegenerative diseases. The glial scar is a result of the astrocyte response to CNS injury. It is made up of many components creating a complex environment in which astrocytes play various key roles. The glial scar is heterogeneous, diverse and its composition depends upon the injury type and location. The heterogeneity of the glial scar observed in different situations of CNS damage and the consequent implications for axon regeneration has not been reviewed in depth. The gap in this knowledge will be addressed in this review which will also focus on our current understanding of central axonal regeneration and the molecular mechanisms involved. The multifactorial context of CNS regeneration is discussed, and we review newly identified roles for components previously thought to solely play an inhibitory role in central regeneration: astrocytes and p75NTR, and discuss their potential and relevance for deciding therapeutic interventions. The article ends with a comprehensive review of promising new therapeutic targets identified for axonal regeneration in CNS and a discussion of novel ways of looking at therapeutic interventions for several brain diseases and injuries.